Meningkatkan Pemahaman Peserta Didik Terhadap Materi Ekosistem Melalui Model Discovery Learning - ., Ani Anjarwati; ., Ika Putri Fadilah; ., Adenita Faradilla; ., Devi Puspita; ., Uul Zahro Aulia (Jurnal Pendidikan, Sains Dan Teknologi, 2022)
The development of HOTS (Higher Out Thinking Skills) based questions is very important to be developed in elementary schools to assist students in developing higher order thinking skills. This study aims to develop test questions proposed by Bloom's taxonomy, namely from C4 (analyze), C5 (evaluate), and C6 (create). Based on the results of PTK or classroom action research at SDN Sukabumi 2, Probolinggo City, it was found that the Discovery Learning method made fifth grade students understand what was conveyed by the author about natural science subjects on ecosystems through power point learning media and learning videos. So the writer wants to test the ability of fifth grade students by giving Pre-Test and Post-Test questions. From the pre-test questions based on the cognitive domain at the LOTS level, students managed to get the highest score, namely 90 in the "good" category. This means that students can already understand what the teacher is teaching using the PjBL method. Meanwhile, from the Post Test questions based on the cognitive domain at the HOTS level, students managed to get the highest score of 96 in the "very good" category. So it is known that the author uses the Discovery Learning method which is very suitable to be applied to fifth grade students regarding natural science subject ecosystem materia.